2005
DOI: 10.1002/nau.20111
|View full text |Cite
|
Sign up to set email alerts
|

Screening test model using duration of labor for the detection of postpartum urinary retention

Abstract: A screening test model using the duration of labor can be constructed to predict PUR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 33 publications
0
10
0
4
Order By: Relevance
“…En effet, durant l'accouchement, la pression prolongée de la tête foetale sur les tissus maternels peut entraîner un oedème des tissus, des lésions nerveuses, musculaires au niveau du plancher pelvien et du détrusor, cela favoriserait une RAU du postpartum [3,4,10,11]. On comprend que chez une primipare, la durée du travail et le temps de l'expulsion étant plus longs que chez la multipare, le risque de RAU du postpartum soit plus élevé [4,6,8,11,12].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En effet, durant l'accouchement, la pression prolongée de la tête foetale sur les tissus maternels peut entraîner un oedème des tissus, des lésions nerveuses, musculaires au niveau du plancher pelvien et du détrusor, cela favoriserait une RAU du postpartum [3,4,10,11]. On comprend que chez une primipare, la durée du travail et le temps de l'expulsion étant plus longs que chez la multipare, le risque de RAU du postpartum soit plus élevé [4,6,8,11,12].…”
Section: Discussionunclassified
“…Certains auteurs rapportent que la durée du travail, si elle est supérieure à 12 heures, est le seul facteur de risque de RAU du postpartum : les autres facteurs de risques, comme la primiparité, le mode d'accouchement, l'analgésie péridurale et l'épisiotomie pourraient être, soit la cause, soit la conséquence de la durée du travail, soit des facteurs de confusion [3,12].…”
Section: Discussionunclassified
“…On the other hand, it has been shown that even a single episode of overdistension can damage the detrusor muscle of the bladder and its function and could be the reason for long-term sequelae [5] . As for screening for PUR, Yip et al [6] recommend first to screen out the patients with a labor duration of ! 700 min; then they should undergo an ultrasound screen to estimate their PVRBV.…”
Section: Discussionmentioning
confidence: 99%
“…Bir başka çalışmada ise oksitosin uygulaması, uzamış doğumun 2.evresi, doğumda vakum kullanılması ve iri bebek PİR ihtimalini arttır-dığı saptanmıştır (10). Yip ve ark ise 700 dakikadan fazla uzun süren doğum eylemlerini PİR risk faktörü olarak tanımlamıştır (23). Kerman ve ark.…”
Section: Etyoloji̇ and Ri̇sk Faktörleri̇unclassified
“…Fakat sezaryen sonrası oluşan postoperatif ağrı ve hareketsizlik PİR oluşumu-nun kolaylaşmasını sağlayabilmektedir (29). Birçok çalışmada iri bebek doğumunun PİR ile ilişkisi ortaya konulamamışken (5,8,14,23) literatürde iri bebekli annelerle PİR ilişkilen-dirilebilmiştir (6,15). Carely ve ark tarafından kontrollü çalışmada primipar kadınlarda multiparlara göre daha sık PİR saptanmıştır.…”
Section: Etyoloji̇ and Ri̇sk Faktörleri̇unclassified